Pengaruh Penambahan Serat Kawat Steel Wool Terhadap Kuat Tarik Beton - Mohammad Yogi Mulyadi; Dendi Yogaswara (Institut Teknologi Garut, 2026)
Concrete is a construction material that has high compressive strength but relatively low tensile strength, so certain materials need to be added to increase its tensile strength. One method that has been widely developed in concrete technology is the use of fibers as additives. This study aims to determine the effect of adding steel wool fiber pieces on the splitting tensile strength of concrete at variations of 0%, 1%, 2%, and 3% of the total mixture weight. The concrete used had a planned strength of f'c 20 MPa with a test age of 28 days. The test specimens were cylinders with a diameter of 15 cm and a height of 30 cm, while the research method used was an experiment with a research duration of two months. The test results showed that normal concrete (0%) had a splitting tensile strength of 2.72 MPa. The addition of 1%, 2%, and 3% steel wool resulted in splitting tensile strengths of 1.87 MPa, 1.75 MPa, and 1.30 MPa, respectively. Overall, the results showed that the addition of steel wool fibers in the variations used tended to decrease the splitting tensile strength of the concrete.